Contemporary World of Young Adults in the ?Girls? Series from the Andragogic Perspective - Chmielarz, Agata (INSTED: Interdisciplinary Studies in Education & Society, 2019)
In recent years the process of entering adulthood underwent multiple social changes and faced the necessity of redefinition. The article presents an andragogic reflection on the contemporary world of young adults presented in the series "Girls". The text includes the description of popular culture as a space for education and socialisation and sources of knowledge about society. Then, the period of early adulthood as a concept used both in psychological and andragogic literature was characterised. Also the place of the "Girls" series in the contemporary and cultural debate was presented. The attempt of analysing the social life spaces of young adults presented in the series enabled the interpretation of the world of contemporary young adults. I pinpointed differences that took place in the way of comprehending adulthood and development tasks specific for that period in the contemporary generation of young adults.